Synsedimentary to early diagenetic rejuvenation of barite-sulfides ore deposits: Example of the Triassic intrakarstic mineralization in the Lodève basin (France). (September 2020) - Laurent, D.; Lopez, M.; Combes, P.-J.; Guerrot, C.; Spangenberg, J.E.; Gaucher, E.C.
Abstract: The exhumed Lodève Basin (Hérault, France) provides a rich suite of outcrops showing diagenetic Ba–Pb–Fe–Cu fronts trapped in karst system in Cambrian dolomites during the Triassic post-rift exhumation of the basin. The sedimentological analysis on 10 sites in the basin reveals that barites-sulfides fronts formed during humid-arid climate fluctuations and the emplacement of a shallow lake environment. The fabric of ore deposits, the microthermometry of fluid inclusions entrapped within barites and the strontium/sulfur isotopic compositions of barite-sulfides associations indicate two distinct groups of mineralizations, Type I and Type II, which are contemporaneous but resulting from different processes. The synsedimentary mineralization of the Type I, the presence of only primary single-phase liquid fluid inclusions within barite crystals and the gradual increase of δ 34 S for both barites and chalcopyrites with depth (from −7 to +18.9‰ V-CDT) suggest ore precipitation close to the vadose zone under bacterial sulfate reduction (BSR) in a confined sulfate-rich playa lake aquifer. The similar 87 Sr/ 86 S ratios between barites and the overlying Triassic evaporites indicate that the barium and strontium derived directly from the overlying sulfate-rich lake. For the Type II, the high homogenization temperature of fluid inclusions entrapped within barite (modal Th between 60 and 80 °C) and the association with hydrocarbon markers, confirm the participation of deeper basinal brines in addition to downward percolating sulfates derived from the lake environment. The high positive values of δ 34 S for both barites and sulfides are typical of a precipitation linked to the combined action between anaerobic oxidation of methane and sulfate reduction (AOM-SR) at the sulfate-methane transition zone (SMTZ) during hydrocarbon migration. Similar 87 Sr/ 86 Sr ratios between Middle Triassic barites and previous Late Permian barites confirm that the source of metals precipitated at the SMTZ originated from the dissolution of anterior ore deposits located in the sulfate-depleted zone. This study links very shallow metallogenesis processes to reworking of MVT ore deposits by the action of sulfate-reducing bacteria around hydrocarbon seeps in a karstic environment. Highlights: Barite-sulfides fronts in meteoric karsts during the Triassic post-rift burial of the Lodève Basin (Hérault, France). Karstology/sedimentology coupled with analyses of texture, fluid inclusions and sulfur/strontium isotopes in ore deposits. Synsedimentary to early diagenetic continental mineralizations at the sulfate-methane transition during hydrocarbon ascent. Metallogenic model: karst dynamics, climate changes, metals and hydrocarbon migration, bacterial mediation.